An airway organoid is forever. (4th February 2019) - Paschini, Margherita; Kim, Carla F
Abstract : In the last decade, the generation and maintenance of organotypic structures has been propelled to the center stage of biomedical research. In the lung, a variety of protocols has been devised to generate organoids mimicking lung structures, but most methods with human cells have complicated lengthy protocols or a progressive decline in differentiation potential and physiological function with increasing passaging. A new study from Sachs et al (2019) seeks to solve these issues, providing a versatile methodology to efficiently isolate, indefinitely culture, and manipulate human airway organoids, potentially allowing the in vitro modeling of a plethora of lung diseases. Abstract : A new methods resource reports long‐term propagation of human lung epithelium as three dimensional organoids which can be exploited for disease modeling.